Field data on plant growth and insect damage on the noxious weed Solanum eleaegnifolium in an unexplored native range - Rupesh R. Kariyat; Jesus Chavana (Data in Brief, 2018)
In this data article, we provide a novel data set on plant growth, insect damage levels, and herbivore community of the noxious and invasive weed Solanum eleaegnifolium (Solanaceae). The data is collected from disturbed and un-disturbed urban populations of the species from one of its unexplored native range in Southern United States (South Texas). The data include plant height measurements, insect damage levels, GPS coordinates of the populations, and their disturbance status. Additional data includes the number of chewing herbivore (specialist herbivore Texas potato beetle (Leptinotarsa texana; Chrysomelidae), their eggs, and any lepidopteran caterpillars found on the plants.